Effect of infertility causes related to gender differences on Women's distress levels among patients utilizing a Turkish university hospital. Issue 5 (28th April 2020) - Durgun Ozan, Yeter; Duman, Mesude
Abstract : Purpose: This study aimed to examine the effect of causes of infertility related to gender differences on the distress level of women who were treated for infertility. Design/methodology/approach: This is a cross-sectional, descriptive study. The sample consisted of 314 women who were treated for infertility between September 2016 and June 2017. Data were collected as "Sociodemographic Characteristics Form" and "Infertility Distress Scale." Findings: A statistically significant difference was found between the mean distress scores of the women for whom the reason for infertility was related to a female factor, and of the women for whom this reason was related to a male factor. Research limitations/implications: The situation should be determined with quantitative studies, and the reason for the differences should be determined with qualitative studies. Practical implications: Infertility nurses should develop a care plan that ensures that couples understand their feelings, and which enhances their mutual respect and partnership. Social implications: The study highlights the importance of cultural awareness in the care of infertile couples. Originality/value: The authors highlight some important aspects about the gender difference on women's distress level.